2019
DOI: 10.1021/acs.energyfuels.9b00595
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Driven Variations in the Depositional Environment and Organic Matter Accumulation of Lacustrine Mudstones: Evidence from Organic and Inorganic Geochemistry in the Biyang Depression, Nanxiang Basin, China

Abstract: The influence of the paleoclimate on the organic matter (OM) accumulation and depositional process in the third member of the Hetaoyuan Formation shales is unclear in the Paleogene lacustrine systems in the Biyang Depression, Nanxiang Basin, Eastern China. Here, inorganic and organic geochemical analyses were performed on samples from a 25 m profile to examine the effects of paleoclimate change on the depositional environment and OM accumulation within this interval. Based on mineralogical and geochemical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The relative composition of C 27 , C 28 , and C 29 regular steranes can reflect the source of organic matter input. Previous studies have found that C 27 sterane indicates the source of aquatic organisms, C 28 sterane is related to diatoms, and C 29 sterane indicates the source of higher organisms. According to the regular sterane triangle of C 27 –C 28 –C 29 (Figure ), the source rocks of Taodonggou group are mainly distributed in estuarine bay and terrestrial, and a few are distributed in open marines. The corresponding biological sources are plankton and terrestrial higher plants .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relative composition of C 27 , C 28 , and C 29 regular steranes can reflect the source of organic matter input. Previous studies have found that C 27 sterane indicates the source of aquatic organisms, C 28 sterane is related to diatoms, and C 29 sterane indicates the source of higher organisms. According to the regular sterane triangle of C 27 –C 28 –C 29 (Figure ), the source rocks of Taodonggou group are mainly distributed in estuarine bay and terrestrial, and a few are distributed in open marines. The corresponding biological sources are plankton and terrestrial higher plants .…”
Section: Discussionmentioning
confidence: 98%
“…The main peak carbon of n -alkanes can indicate the input of organic matter. When the main peak carbon is low carbon number (<20), it indicates the source of algae and other lower aquatic organisms. When the carbon number is high (>C 23 ), the distribution characteristics of the peak type indicate the input of terrestrial higher plants. , The main carbon peaks of Taodonggou group source rocks in the study area are n C 17 , n C 18 , n C 19 , n C 21 , n C 23 , and n C 29 , indicating that the organic matter input of the source rocks is mixed source input, and the ratio ∑C 21 –/∑C 22 + of source rocks can characterize the relative input of lower aquatic organisms and terrestrial higher plants .…”
Section: Discussionmentioning
confidence: 99%
“…12−14 Furthermore, due to limited geographic size, the lacustrine environment and deposits are more easily influenced by paleoclimate change than the marine environment. 15 Although the paleoclimates between J 2 d 7 oil shale and dark shale in the study area have been well-researched before, 16 the influence of the related geological process on the development of radioactive elements and OM in lacustrine shale was not clearly understood, including the water properties, provenance chemical weathering, terrigenous materials input, primary paleoproductivity, and so forth. Yang (2017) also emphasized that instead of OM, the uranium content in alum shale was controlled by physicochemical conditions of the depositional environment.…”
Section: Introductionmentioning
confidence: 94%
“…Red dashed lines with arrows show the premetasomatized CIA values for the samples. 16 Geofluids the bottom to top in the M3 section, the paleoclimate exhibits a relatively stable semiarid condition (Figure 3). [13,20,73].…”
Section: 3mentioning
confidence: 99%
“…Organic-rich mudstones in lacustrine basins can be regarded as favorable hydrocarbon source rocks or direct unconventional petroleum resources (e.g., shale oil and shale gas) [14,15]; however, their formation processes are much more complicated than those in marine basins, since terrigenous influx and paleoclimate can exert a substantial influence on the evolution of restricted lacustrine basins [16,17]. Fortunately, continuous geochemical data of lacustrine sediments are used to reconstruct the depositional paleoenvironments at that time, which contributes to a better understanding of OM enrichment in lacustrine basins [9,12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%